2018
DOI: 10.17581/bp.2018.07102
|View full text |Cite
|
Sign up to set email alerts
|

Mycolith (fungal phytolith) morphotypes and biosilification of proteins in wood-destroying and pileate fungi

Abstract: The process of biomineralization in fungi is discussed for the first time. The results of a comprehensive study of fungal phytoliths (mycoliths) using optical micro scopy and RAMAN spectroscopy are presented. The RAMAN spectrum con tains bands of crystalline silicon dioxide and amorphous silica. In all types of fungi and trees examined, two morphotypes of phytolite particles were identified with an aid of microsco pe, oblong and spherical. The rest of the particles were considered formless. To explain the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The occurrence of high Si contents in a single subfamily of orchids (one of the largest plant families globally) is not unique: 29 of the 412 angiosperm families include both Si-rich and Si-poor species (7% of all angiosperm families, but 17% of families for which data exist) [ 23 ]. Finally, it should be noted that although most research revolves around seed plants, silicon and phytoliths are common and abundant in many bryophytes and pteridophytes [ 122 , 172 , 176 , 177 , 178 ] (phytolith-like “mycoliths” also occur in fungi [ 179 ]), sometimes in contents that surpass those found in Poaceae species [ 172 ].…”
Section: The Variability Of Silicon In Plantsmentioning
confidence: 99%
“…The occurrence of high Si contents in a single subfamily of orchids (one of the largest plant families globally) is not unique: 29 of the 412 angiosperm families include both Si-rich and Si-poor species (7% of all angiosperm families, but 17% of families for which data exist) [ 23 ]. Finally, it should be noted that although most research revolves around seed plants, silicon and phytoliths are common and abundant in many bryophytes and pteridophytes [ 122 , 172 , 176 , 177 , 178 ] (phytolith-like “mycoliths” also occur in fungi [ 179 ]), sometimes in contents that surpass those found in Poaceae species [ 172 ].…”
Section: The Variability Of Silicon In Plantsmentioning
confidence: 99%
“…It is more aggressive for microstructures and as we believe it leads to the destruction of large formations, especially that they are very thin -hundreds of nm. It is unlikely that the formless microparticles with an infinite variant of morphotypes may have some common function in all plants from red algae and lichens to bilobed and even fungi [5]. A typical morphometric research shows the phytoliths size from 10 to 150 μm with a mode around 20-60 μm [8,4].…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown that silicon formations exist in all taxa of plants, ranging from red algae and lichens, (e.g., Chondrus crispus) having proteins that are partially similar to proteins of the biosilification of sponges, diatoms and higher plants [2; 3; 4], and even in mushrooms [5]. With regard to distant taxa, the differences in the phytolite composition are quite explicable.…”
Section: Introductionmentioning
confidence: 99%